Exercise training alters resting brain-derived neurotrophic factor concentration in older adults: A systematic review with meta-analysis of randomized-controlled trials - Farhad Gholami; Javad Mesrabadi; Mohadeseh Iranpour; Adel Donyaei (Experimental Gerontology)
This systematic review with meta-analysis investigated the effects of exercise training on brain-derived neurotrophic factor (BDNF) in older adults. Electronic databases of PubMed, Web of Science and Scopus were searched for studies investigating the effect of exercise training ≥4 weeks on resting BDNF levels in older adults. A standardized mean difference (SMD) was generated through random effects model. Thirty-five randomized-controlled trials met the inclusion criteria. Exercise training significantly increased resting BDNF levels [SMD = 0.56 (95 % CI 0.28 to 0.85)] both in plasma (SMD = 0.63) and serum (SMD = 0.54). Regarding exercise modality, aerobic (SMD = 0.48), resistance (SMD = 0.76) and combined exercise training (SMD = 0.55) increased BDNF levels. Exercise training with the duration of 12 weeks (SMD =0.65), moderate-to-vigorous (SMD = 0.83) and vigorous intensity (SMD = 0.71), and 3–4 sessions per week frequency (SMD = 0.78) yielded the largest effects on BDNF elevation. Since BDNF represents a fundamental contribution in neuronal processes and is linked to brain health, exercise training may help delay aging-related neuro-degenerative processes. Registration number: CRD42024499195.